A dataset for soil organic carbon in agricultural systems for the Southeast Asia region - Gomez, Federico; Carcedo, Ana; Mean, Chan Makara; Reyes, Manuel; Hok, Lyda; Tivet, Florent; Seng, Vang; Vara Prasad, P. V.; Ciampitti, Ignacio (Scientific data, 2024)
The determination of changes in soil organic carbon (SOC) content under different cropping systems is necessary for policy development oriented towards soil conservation, C sequestration, and future C credit markets. The aim of this study was to generate an open SOC dataset resulting from a systematic literature search related to the agricultural systems for Southeast Asia. The dataset has 209 articles and 4341 observations on soils of cropping systems in this region from articles published between 1987 and 2023. This dataset included different management practices, land uses, soil sampling depth, and length of SOC content assessment. In addition, inherent features of crop production reported in the experiments were included in the dataset. This dataset can be applied to quantify and compare the impact of different land uses or management practices on SOC content, providing foundational knowledge towards identifying sustainable practices. Lastly, it is a useful guide for future regional SOC sequestration policies and the development of C credit markets.